Fit-for-purpose environmental modeling: Targeting the intersection of usability, reliability and feasibility. (February 2022) - Hamilton, Serena H.; Pollino, Carmel A.; Stratford, Danial S.; Fu, Baihua; Jakeman, Anthony J.
Abstract: Although it is widely acknowledged as a fundamental principle that models be fit-for-purpose, there remains lack of clarity on what this notion actually means and therefore how it is achieved. We contend that fitness-for-purpose must go beyond the functional use of the model to include its management, problem and project contexts. Accordingly, we propose a practical framework that considers fit-for-purpose modeling as the intersection of three requirements, in that the modeling be: useful, addressing the needs of the end user; reliable, obtaining an adequate level of certainty or trust; and feasible, within practical constraints of the project. Modeling choices, including the selection of spatial and temporal scales, system features and processes to include, and the type of model, can be better informed when the bounds of these fit-for-purpose requirements are defined. We focus on modeling in decision and management support settings, and demonstrate the framework with ecohydrological models designed for managing environmental flows. By explicitly linking its intended functional use and context to modeling choices, this framework can facilitate the design and development of environmental models that more effectively bridge science and management. Highlights: Model purpose includes not only its functional use but also its management, problem and project contexts. Designing a fit-for-purpose model is about making choices that ensure it is useful, reliable and feasible. A fitness-for-purpose framework is proposed to provide guidance in modeling development and evaluation. Modeling choices include selection of scales, system features and processes, type of model and evaluation method. The framework and process are demonstrated with environmental flow models.